Effectiveness and Students’ Perception of the Use of Pre-reading Strategies and Summaries: A Case Study of Adult EFL Students in a Reading Comprehension Course - Barrantes Torres, Daniela (Revista de Lenguas Modernas, 2018)
This study is aimed at providing an answer to the questions of how the completion of pre-reading exercises and summaries can enhance learners’ reading comprehension and what their perceptions of the usefulness of these tools to read texts in English are. Students completed different pre-reading exercises including the adapted version of the K-W-L organizer to establish a connection between their background knowledge and the texts. They also wrote summaries in order to check their understanding of the gist of the texts. The review of the literature makes reference to the bene ts of using pre-reading strategies and summaries to better understand texts. The information gathered shows that learners were able to understand the main ideas of the texts, but some of them still had difficulties to analyze speci c details in order to carry out the course-related tasks. The results also indicate that students had contrasting points of view about the usefulness of both strategies to read texts in English be- fore and after the interventions. Este estudio responde a las preguntas de cómo la realización de ejercicios de prelectura y resúmenes pueden mejorar la comprensión de lectura de los educandos y cuál es su percepción de la utilidad de estas herramientas para leer textos en inglés. Los estudiantes completaron diferentes ejercicios de prelectura, incluida la versión adaptada del diagrama K-W-L con el n de establecer una conexión entre su conocimiento previo y los textos. Además, escribieron resúmenes para comprobar su comprensión de la idea central de los textos. El marco teórico hace referencia a los bene cios de usar estrategias de prelectura y resúmenes para una mejor comprensión. Los datos obtenidos muestran que los estudiantes fueron capaces de comprender la idea principal de los textos pero algunos de ellos tuvieron di cultad en analizar detalles especí cos para llevar a cabo las asignaciones del curso. Los resultados también indican que los alumnos tuvieron puntos de vista contrastantes sobre la utilidad de ambas estrategias para leer textos en inglés antes y después de las intervenciones